Effect of different clipping times on forage quality of three cereal crops at two locations of sulaimani region - Tawfiq, Sherwan Esmaeel; Muhammed, Sanarya Rafiq (Sulaimani Journal for Pure and Applied Sciences, 2015)
The present study was conducted in Sulaimani Region at two different locations, Qlyasan and Kanipanka during the winter season of 2010-2011, to determine the effect of different clipping times{clipping at 80 days after sowing (1st clipping time), clipping at 90 days after sowing (2ndclipping time), clipping at 100 days after sowing (3dclipping time), and clipping at 110 days after sowing (4th clipping time) as well as control (no clipping)}on forage quality of three cereal crops (wheat, barley and triticale) at Qlyasan location and the following day similarity at Kanipanka location. The design was split plot within factorial experiment, the cereal crops were implemented in the main plots and arranged with complete randomized design (CRBD) and replicated three times, where the clipping times were implemented in sub plots. Means comparison were carried out using least significant difference test (LSD) at 0.05 significant levels. The results of the present study as the average of both locations showed that the fourth clipping time exceeded the other clipping times in the characters: Acid Detergent Fiber (ADF%), Acid Detergent Lignin (ADL%), Neutral Detergent Fiber (NDF%), fiber%, starch% and Mg% with the values of 28.222%, 5.645%, 39.194% , 14.282%, 8.223% and 0.080% respectively, while the first clipping time exhibited maximum values of 14.561% , 24.992%, 81.138%, 0.545% , 4.408%, 0.583% and 3.734% for the characters Ash%, protein%, DP%, Ca%, K%, P% and fat% respectively. According to the results of this study we concluded that protein and digestible protein were differed significantly among species, where barley showed its superiority in these characters and most quality traits compared to wheat and triticale, and The quality was diminished as maturity increased, the nutrient composition and forage quality of small grain plants change significantly as the plants develop; therefore, the earlier cutting dates are recommended to achieve this purpose.
Keywords: Forages; clipping times; wheat; barley; triticale; forage quality; Introduction